Language choice and use of Malaysian Tamil Christian Youths: a survey - Leo, Angela Rumina; Abdullah, Ain Nadzimah (Universal Publishers, 2013)
Language choice and use, which refers to the selection of language(s) for diverse purposes in diverse contexts with different individuals or groups, are common but rather vital sociolinguistic phenomena in a multilingual setting. This study integrates Fishman’s (1972 domain analysis to determine the dominant language choice of Tamil Christian youths in Malaysia based on their patterns of language choice and use in the domains of family, friendship, and religion; and to examine the underlying factors that govern their language choice patterns in the selected domains. The data were collected through a questionnaire administered to 60 Tamil Christian youths at a church in Kuala Lumpur; together with 4 face-to-face interviews. SPSS was used to get percentage values and frequencies through descriptive statistics of data from the questionnaire. The findings of the study indicate that the respondents chose and used English, Tamil, and Bahasa Malaysia in the selected domains. The English language was found to be used predominantly in all three domains as a result of the influence of these particular domains; the speakers’ verbal repertoires and those of their addressees; their attitude towards a language and its speakers; motivation; and also their sense of solidarity and social identity.